Predictive Risk Factors for Development of Recurrent Inguinal Hernia in Children - Mohamad Theyab Hamad; Mohammed Atyah Farhan; Hussein Alwan Khalaf (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Background: Hernia is a common surgical problem in children. Usually it requires surgical intervention and one complication of hernial surgery is recurrence of the hernia. Aim of study: To identify the predictive risk factors for recurrence of the hernia and make efforts to avoid the recurrence. Patient and methods: This is a prospective study conducted in Baquba teaching hospital for the period from the 1st of Jan. 2020 to the thirty of June 2024, included (188) cases. Open Herniotomy done for all of them. 163 patients (86.7%) were male and 25 patients (13.2%) female. 104 (55.3%) cases in right side and 82 case (43.6%) in left side and only (2) patients (1.06%) have bilateral inguinal hernia. Result: The age of the patient range from one month up to (14) years. Mean age was (3.12) years. Follow up period for one year for all patients to detect the recurrence. 7 patients (3.7%) develop recurrent hernia. 3 patients less than one year, 3 patients from 6-10 years and one patient is more than 11 years. 18 (9.57%) have thin sac and 3 (16.6%)of them develop hernia while those with normal wall thickness only one patient (0.58%) develop hernia. 15 patients (7.79%) have wide neck sac more than 1.5cm 2 (13.3%)of them develop hernia and only one patient (0.57%) with narrow sac neck less than 1.5cm develop hernia. Conclusion: Thin wall hernia sac and wide neck hernia sac more than 1.5cm are more predictive risk factors for developing recurrent inguinal hernia in children.